The Effect Of Progressive Muscle Relaxation Therapy On Reducing The Stress Level Of Inmates In Class II B Kudus Detention Center - Sri Hindriyastuti; Noor Faidah; Gardha Rias A (International Journal Of Health Science, 2023)
The number of inmates in the detention center has increased, resulting in increased levels of stress on inmates namely mild stress levels (11.1%) and moderate stress (33.3%) in 2015. All the pressure that occurs on prisoners in prison will result in mental and physical illness and prolonged stress will result in mental disorders such as depression, anxiety and even psychotic disorders. Stress management is used to overcome and reduce stress levels. Progressive muscle therapy is a therapeutic that is superior to other therapies because it is the cheapest and it's easy to do independently and shows the importance of restraining stress responses by trying to relieve conscious muscle tension. The design of this study used a pre - experimental design with a design of one group pre test - post test design. The population in this study were criminals in the Prison of Class II B Kudus. The sampling technique uses total sampling so that the sample size is 13 respondents. Data was collected using observation of stress levels and then analyzed using paired T test. The result of the paired T test showed that there was a significant effect between progressive muscle relaxation therapy on the reduction of stress levels in criminals in the Prison Class II B Kudus with a p-value of o,oo1 (p<0.05). There is the Effect of Progressive Muscle Relaxation Therapy on Drecreasing Stress Levels of criminal in Prison Class II B Kudus.